The Sleep Disorders And Depression Symptoms Among Hospitalized COVID-19 Patients - Febriawati, Juwita; Astuti, Triwahju; Djajalaksana, Susanthy; Listyoko, Aditya Sri (Universitaas Brawijaya, 2025)
Introduction: Sleep disorders are found to be associated with hypertension, diabetes, cardiovascular disease and obesity, and can affect quality of life. Evaluation of sleep disorders and risk of depression in hospitalized COVID-19 patients have not been widely studied. The purpose of this study was to identify, evaluate, and analyze of sleep disorders and depression symptoms in hospitalized COVID-19 patients according to their severity and PaO2/FiO2 ratio. Case Report: A total of 35 patients with mild and moderate COVID-19 were given a questionnaire consisting of Epworth Sleepiness Scale (ESS) and Beck Depression Inventory (BDI), which was then analyzed together with the patient's blood gas analysis. Categorical data was compared using Chi Square Test, while the relationship between the continuous variables were measured with Pearson correlation test. A two-sided p value < 0.05 was considered statistically significant. About 42,85% and 62,9% COVID-19 patients were found to have sleep disorders and depression symptoms respectively. There were no significant differences between sleep disorders and the severity of COVID-19 (P=0.118) as well as PaO2/FiO2 ratio (P=0.411). Similarly, depression symptoms was not significantly different according to the severity of COVID-19 and PaO2/FiO2 ratio obtained with P=0.083 and P=0.061 respectively. Correlation test showed no significant correlation between sleep disorders and severity as well as PaO2/FiO2 ratio with r=0,274(p=0,111) and r=0,041(p=0,814) respectively. Likewise, negative correlation was found between depression symptoms and severity of COVID-19 (r=0,218;p=0,258) as well as PaO2/FiO2 ratio (r=0,078, p=0,057). Conclusion: In hospitalized COVID-19 patients, sleep disorders and depression were found, but there was no significant differences and correlation between sleep disorders and depression symptoms with the severity of COVID-19 and PaO2/FiO2 ratio.